Environmental exposure to per- and polyfluoroalkyl substances and childhood congenital heart disease: a mixed analysis - Jiao, Xianting; Zhao, Liqing; Xu, Yuejuan; Gao, Jiawei; Tang, Weifeng; Wu, Yurong; Yang, Ling; Huang, Jihong; Guo, Yi; Sun, Kun; Chen, Sun (Frontiers in Public Health, 2025)
BackgroundPer- and polyfluoroalkyl substances (PFAS) exposure is associated with various health risks. However, limited research has explored their potential connection with congenital heart disease (CHD).ObjectiveThis study aimed to investigate the relationship between different types of PFAS and childhood CHD using a mixed analysis approach.MethodsA hospital-based case–control study was conducted involving 282 children with CHD and 282 control participants. Plasma samples were analyzed for 19 PFAS congeners. Logistic regression, Bayesian kernel-machine regression (BKMR), and weighted quantile sum (WQS) models were employed to assess the association between individual PFAS and PFAS mixtures with CHD risk.ResultsAnalysis of 564 subjects revealed higher plasma concentrations of various PFAS compounds in the CHD-group. Logistic regression identified significant associations between CHD risk and specific PFAS, notably 6:2 Chlorinated polyfluoroalkyl ether sulfonic acid (6:2 Cl-PFESA) (OR = 1.65; 95%CI: 1.40–1.94), 8:2 8:2 Cl-PFESA (OR = 1.69; 95%CI: 1.69–2.19), Perfluorobutanoic acid (PFBA) (OR = 2.68; 95%CI: 2.28–3.15), Perfluorobutane sulfonic acid (PFBS) (OR = 2.38; 95%CI: 1.77–3.22), Perfluorohexanoic acid (PFHxA) (OR = 2.62; 95%CI: 1.99–3.45), and Perfluorotetradecanoic acid (PFTeDA) (OR = 2.18; 95%CI: 1.81–2.63). BKMR analysis confirmed these findings. WQS analysis emphasized PFBA, 8:2 Cl-PFESA, PFHxA, and PFTeDA as key contributors to the association between PFAS mixture exposure and CHD risk.ConclusionExposure to PFAS mixtures was associated with an increased risk of CHD in children, with 6:2 Cl-PFESA, 8:2 ClPFESA, PFBA, PFHxA, and PFTeDA playing significant roles.